The Analysis of the Relationship between Corporate Social Responsibility and Financial Performance of Company - Palaščáková, Daniela; Michalska, Monika (Zielona Góra: Faculty of Economics and Management Press)
Corporate SCorporate Social Responsibility (CSR) has been forming very dynamically and intensively for several decades. The rapid development, as well as the relatively large scope of this concept, which is cross-sectionally related to a number of different social disciplines, so far causes a very significant terminological inconsistency.
Keywords: Corporate Social Responsibility (CSR); economic pillar; indicator; company; profit